Analisis Nilai-Nilai Pendidikan Karakter dalam Kitab Ngudi Susilo Karya KH. Bisri Mustofa dan Relevansinya di Era Modern - Mylanadia; Aisyi, Hithna Rohadatul; Astuti, Dewi (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2025)
This study investigates the character education values contained in Ngudi Susilo, a poetic work by KH. Bisri Mustofa, and examines their relevance in the context of modern education. Using a qualitative descriptive approach through library research, this study explores the moral teachings embedded in the text and their significance for contemporary character formation. The findings reveal nineteen character values reflected in the verses, including religiosity, responsibility, humility, discipline, patience, self-awareness, contentment (qona’ah), politeness, justice, compassion, love of peace, diligence, obedience, enthusiasm, love of reading, respect for parents (ta’dzim), remembrance of God (dzikir), patriotism, and civility. These values are conveyed through simple yet profound poetic expressions written in Arabic Pegon script and Javanese language, aiming to internalize noble moral behavior. The study highlights that these values remain highly relevant to the moral and ethical challenges faced in modern society, which often emphasizes intellectual achievement over moral development. Integrating these character values within modern education can balance cognitive advancement with emotional and spiritual maturity. Thus, Ngudi Susilo provides a timeless and contextually adaptable framework for strengthening moral education, promoting holistic character development, and fostering a generation that is intellectually competent, spiritually grounded, and socially responsible.